2018
DOI: 10.1093/jbcr/iry041
|View full text |Cite
|
Sign up to set email alerts
|

Multiregional Utilization of a Mobile Device App for Triage and Transfer of Burn Patients

Abstract: Technology and telehealth have the potential to optimize burn care in areas limited by lack of expertise and geographic distance from a Burn Center. This study reports a multicenter, multiregional experience using a mobile phone app to facilitate triage of patients by allowing referring providers to send encrypted photos, thus enhancing the telephone consultation process. A retrospective review was conducted on referrals from August 2016 to July 2017 at three regional Burn Centers that utilize the same mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Regarding follow-up, monitoring, and rehabilitation of burn patients, 14 articles considered TH as a potentially beneficial tool [ 2 , 30 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding follow-up, monitoring, and rehabilitation of burn patients, 14 articles considered TH as a potentially beneficial tool [ 2 , 30 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies found shortcomings relating not only to ethical, legal, and regulatory issues but also to security, confidentiality, and privacy. They also noted that limitations existed regarding interoperability and compatibility between systems using TH [ 2 , 7 , 12 , 15 , 16 , 17 , 19 , 21 , 23 , 27 , 28 , 33 , 35 , 36 , 37 , 38 , 40 , 42 , 45 , 46 ]. Besides these shortcomings, the impact of which means that such technologies run into complex implementation difficulties, there is a need for more studies to investigate how significant improvements could be achieved in the clinical efficacy and cost-efficiency associated with their use.…”
Section: Resultsmentioning
confidence: 99%
“…Em recente revisão integrativa acerca dos impactos de sistemas eletrônicos de comunicação no setor saúde, apenas plataformas vinculadas à web foram reportadas (Muniz et al, 2021). Buscas na literatura específicas para aplicativos revelaram diversos projetos de desenvolvimento de apps com cunho assistencial, prevendo suporte remoto para profissionais generalistas em áreas distintas, com destaque para a condução de casos de queimaduras (Blom et al, 2018;Martinez et al, 2018;Wallis et al, 2016;Wiktor et al, 2018) e para a área de dermatologia (Hasbún Zegpi, et al, 2020;Pecina, et al, 2017;Rizvi, et al, 2020;Yang, et al, 2019). Junto às lojas virtuais de aplicativos App Store e Google Play, a busca de anterioridade encontrou duas plataformas bastante semelhantes, ofertadas para discussão de casos clínicos entre profissionais de saúde de todo o mundo através do compartilhamento de fotos e troca de comentários nas imagens: o app canadense Figure 1 (https://www.figure1.com, recuperado em 16 de outubro, 2021), e o britânico MedShr (https://en.medshr.net, recuperado em 16 de outubro, 2021).…”
Section: Introductionunclassified